Tingkat Kompetensi Wanita Tani Dalam Budidaya Tanaman Sayuran - Dasmin Sidu; Ima Astuty Wunawarsih; Reny Setiawati (Fakultas Pertanian Universitas Halu Oleo, 2021)
The objectives of this study were: (1) to analyze the competence of female farmers in vegetable cultivation and (2) to analyze the relationship between the characteristics of respondents and the competence of women farmers in cultivating vegetable crops. This research was conducted in Wonua Village, Konda District, South Konawe Regency. The determination of the research location was carried out purposively (purposive sampling), with the consideration that Konda District is the center for vegetable production and 50% of the people in Wonua Village cultivate vegetable crops. And the farmer's wife is directly involved in vegetable farming. The number of samples in this study were 30 vegetable farmers. The data analysis used quantitative derivative analysis method and Spearman Rank Correlation analysis. The results showed that the competence of female farmers in vegetable cultivation was high. There are four identities of respondents that have a significant relationship with the competence of female farmers in vegetable cultivation in Wonua Village. These characteristics include education, farming experience, number of family dependents and farmer cosmopolitanism. Meanwhile, the other three characteristics have an insignificant relationship with the competence of female farmers in Wonua Village.